The Implementation of Think Talk Write Learning Strategy to Improve Student’s Learn Activities in Biology Learning Class X-1 SMA Al Islam 1 Surakarta of 2009/2010 Academic Year - Dwitya Nadia Fatmawati; Slamet Santosa; Joko Ariyanto (BIO-PEDAGOGI, 2013)
The purpose of the research to improve student learning activities in teaching and learnig activities with the implementation of Biology learning strategy Think Talk Write on Environmental Pollution material. This research is a classroom action research. The experiment was conducted in two cycles, with each cycle  consisting of the  planning, observation, evaluation, analysis,  and reflection. Subjects  were  students  of class  XI  SMA  Al  Islam  1 Surakarta  academic  year 2009/2010. Source  of data  derived from  teacher  and  student  information,  observation,  and documentation. Techniques and tools of data collection is a questionnaire, observation, and interviews. Validate  data  using  triangulation techniques  of data  sources. Data  analysis techniques used are qualitative analysis. Research procedure is a spiral model of inter-related. The results showed that the application of learning strategies can improve  student  activities  in biology  learning  in class  X-1 SMA  Al  Islam  1 Surakarta 2009/2010 academic  year. Improved student  learning  activities  can be  viewed through a questionnaire and observation sheet. The average percentage based on observation of student activity  sheets  for 41.90% of pre  cycle, a  cycle  of 73.07% and 87.23%  for  cycle  2.Questionnaire  pre-cycle  calculation results  indicate  student  activity  at  70.49%, a  cycle  of 73.83%, and the second cycle result indicate that student activity of 77.96%. Key Words: Think talk write learning strategy, student activity, biology learning.